SPE Annual Technical Conference and Exhibition 2000
DOI: 10.2118/63255-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Scratch Test: An Attractive Technique for Determining Strength and Elastic Properties of Sedimentary Rocks

Abstract: The Scratch Test is a relatively new technique for determination of mechanical properties of rocks. In a Scratch Test, the surface of the rock is scratched at constant depth (typically less than 1 mm) by a sharp cutter, while the applied forces are being monitored. It is found that these forces are closely related to the mechanical properties of the rock. The Scratch Test thus represents a direct measure on the core material, and provides continuous coverage of data for the entire length of available core mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…Rock stiffness may vary a lot from one location to another, on all length scales. Even within the few centimetres covered by a core plug from a uniform formation, there may be large variations in stiffness (Schei et al 2000). Within 100 m range corresponding to the wavelength of a seismic wave, even larger variations will normally occur due to the presence of different rock types.…”
Section: H E T E R O G E N E I T I E Smentioning
confidence: 99%
“…Rock stiffness may vary a lot from one location to another, on all length scales. Even within the few centimetres covered by a core plug from a uniform formation, there may be large variations in stiffness (Schei et al 2000). Within 100 m range corresponding to the wavelength of a seismic wave, even larger variations will normally occur due to the presence of different rock types.…”
Section: H E T E R O G E N E I T I E Smentioning
confidence: 99%
“…The word intrinsic emphasizes that this energy is strictly used to cut the rock. A strong correlation between intrinsic specific energy and uniaxial compressive strength for various rocks is well established [48,49].…”
Section: Scratch Test Analysismentioning
confidence: 96%
“…The principle of the scratch test is to control and monitor the continuous shearing action induced by the motion of a 3 Geofluids diamond (PDC) cutting tool on the surface of a rock core sample [47,48]. The continuous high-resolution profile of rock strength (UCS) along the core sample is derived from the force acting on the cutter.…”
Section: Scratch Test Analysismentioning
confidence: 99%
“…Richard et al (1998) further demonstrated that the friction coefficient of a scratch test is equal to the intrinsic friction coefficient of the tested rock. Schei et al (2000) analyzed the force acting on a scratch cutter and found that there is a strong correlation between the hardness of rock and scratch measurements. Based on this finding, Schei et al presented a preliminary model for rock hardness evaluation using scratch test results; however, the accuracy of the evaluation model is not very satisfactory.…”
Section: Introductionmentioning
confidence: 99%